Exploring Muscle Energy Technique as A Physiotherapeutic Intervention for Peripheral Facial Palsy: A Pilot Report - Dimpi Phukan; Kangkan Talukdar; Ankur Jyoti Bora (International Journal of Orthopedic Nursing and Practices, 2024)
Background: Peripheral facial palsy results from damage to the peripheral branches of the facial nerve, often presenting as a sudden weakness in the muscles on one side of the face. Research on the application of muscle energy technique (MET) for treating this condition is scarce. Therefore, the aim of this study was to assess the effectiveness of MET in the treatment of peripheral facial palsy. Methods: 15 patients suffering from peripheral facial palsy attending Physical Medicine and Rehabilitation Department for physiotherapy were included in the study to assess their collective impact. The study spanned a duration of 2 weeks, utilizing a combination of muscle energy technique and electrical muscle stimulation as interventions. Treatment duration of one session were approximately 30 minutes. Three measuring tools were taken namely Sunnybrook Facial grading scale((SFGS), House Brackmann Scale (HBS) and Facial Disability Index (FDI). The data collection for the study is conducted on the 1st ,7th and 14th day. Results: There are statistically significant differences between the 1st, 7th, and 14th sessions for FDI-physical function sub-scale, HBS, and SFGS scores, with all mean differences being negative (1st
Keywords: Peripheral facial palsy; facial disability index; house brackmann scale; muscle energy technique; sunny brook facial grading scale